Filosofi Tri Hita Karana dalam Perspektif Keadilan, Love of Money, Gender, dan Religiusitas terhadap Penggelapan Pajak - Pujianto, Pujianto; Indah Pratiwi, Lily (Politeknik Raflesia Press, 2024)
This research aims to determine the influence of perceptions of justice, culture, gender, love of money, and religiosity on tax evasion by highlighting it from the perspective of the Tri Hita Karana philosophy. The sample in this research is Taxpayers registered at KPP Sukomanunggal Surabaya. The sampling method in this research is non-probability, namely convenience sampling. The sample size in this study was determined by mathematical calculations using the Slovin formula. Based on this sampling technique, 150 questionnaires were distributed with QR Codes and Gforms and 129 were returned, while only 100 questionnaires were filled in correctly. The data analysis method used in this research is multiple linear regression with the help of SPSS. The research results show that justice, culture, love of money, and religiosity partially influence tax evasion. Meanwhile, gender has no effect on tax evasion..